Pendampingan Digitalisasi Administrasi dan Pemasaran pada UMKM Keripik Belut Crunchy di Purwakarta: Pengabdian - Rukminingsih, Chinta; Nurwasiyah , Yusi; Junyar, Zihan; Mega Sukmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community-service program aims to enhance the managerial capacity of UMKM Keripik Belut Crunchy through administrative and marketing digitalization. The UMKM faced challenges in financial recording, administrative documentation, and digital marketing. This study uses a descriptive qualitative method through observation, interviews, and documentation. The assistance includes creating a Google Business Profile, training in Excel-based bookkeeping, producing digital promotional media, and standardizing administrative documents. The results show improvements in financial documentation, online visibility, and administrative neatness. The Google Business Profile increased customer engagement, while Excel-based bookkeeping enabled the owner to understand cash flow and business profit. Therefore, administrative and marketing digitalization effectively enhances UMKM professionalism and competitiveness.